Educational Facilities Provision and Maintenance Nexus in Nigeria :The Ekiti-South West Example (American International Journal of Nursing Education and Practice, 2020)
The aim of this study was to assess the provision and maintenance of educational facilities in Ekiti State, Nigeria with a focus on the Ekiti-South West LGA and Community-Based Development Associations in the area. This study adopted the survey research method and used three different sets of a questionnaire to collect research data from the authority of the Ekiti South-West LG Council officials, Community Development Unit of the LG Council and the 61 Community-Based Development Associations (president/secretary) available in the study area and their responses were analyzed using SPSS 21 and presented in simple descriptive tables. The data were analysis using tables, frequency and percentages. From the results of the study, majority of the secondary schools were privately-owned (49.5%), while Nursery/Primary School were mainly Community-Owned (56.0%). However, the present monthly allocation from Federal Government to LGCs is grossly inadequate, and it is not enough to embark on provision and maintenance of educational facilities. Given the findings, there were need to improve the schools through additional appropriation and maintenance of the existing schools; finally, the governments and other stakeholders should inculcate good maintenance culture on our educational facilities for effective management with the intention of promoting high-quality education for the well-being of the nation.